LC-MS/MS metabolomics-facilitated identification of the active compounds responsible for anti-allergic activity of the ethanol extract of Xenostegia tridentata - Suntivich, Rinrada; Songjang, Worawat; Jiraviriyakul, Arunya; Ruchirawat, Somsak; Chatwichien, Jaruwan (PLOS ONE, 2022)
In vivo and in vitro anti-allergic activities of ethanol extract of Xenostegia tridentata (L.) D.F. Austin & Staples were investigated using passive cutaneous anaphylaxis reaction assay and RBL-2H3 cell degranulation assay, respectively. The crude ethanol extract exhibited promising activities when compared with the known anti-allergic agents, namely dexamethasone and ketotifen fumarate. The ethyl acetate subfraction showed the highest anti-allergic activity among various sub-partitions and showed better activity than the crude extract, consistent with the high abundance of total phenolic and flavonoid contents in this subfraction. LC-MS/MS metabolomics analysis and bioassay-guided isolation were then used to identify chemical constituents responsible for the anti-allergic activity. The results showed that major components of the ethyl acetate subfraction consist of 3,5-dicaffeoylquinic acid, quercetin-3-O-rhamnoside, kaempferol-3-O-rhamnoside and luteolin-7-O-glucoside. The inhibitory activity of the isolated compounds against mast cell degranulation was validated, ensuring their important roles in the anti-allergic activity of the plant. Notably, besides showing the anti-allergic activity of X. tridentata, this work highlights the role of metabolomic analysis in identifying and selectively isolating active metabolites from plants.